Infantile haemangioma presenting in combination with a cerebriform naevus sebaceous on the scalp. (1st January 2022) - Chottianchaiwat, S.; Martinez, A. E.; Solman, L.; Petrof, G.
Abstract: Click https://wileyhealthlearning.com/#/online-courses/a54fac75-89f4-4bf5-80a4-19e31765a7a4 for the corresponding questions to this CME article.